A New Costing System in Hospital Management: Time-Driven Activity Based Costing: A Narrative Review - Sina Etemadi; Behzad Mohammadi; Mohammad Javad Akbarian Bafghi; Marjan Hedayati Poor; Mohammad Tasavon Gholamhoseini (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Changes in the hospital environment, technology, and service delivery as well as the increased share of overhead costs have motivated hospital managers to look for useful means of calculating costs. A key element of the health system success is the accurate computation of costs. Determining the exact costs enables managers and policymakers to make proper decisions with regard to optimal allocation of resources. This study explores the results of the activity-based costing model (ABC) and time-driven activity-based costing model (TDABC) in calculating the cost of diagnostic departments in hospitals. Methods: This was a narrative literature review paper. The data was gathered from the earliest documented scientific English and Persian articles, up to 2016, as well as relevant books based on keywords such as Activity Based Costing, Time-Driven Activity Based Costing and hospitals. Finally, a total of 543 studies were obtained after searching, then, to collect the relevant articles, the researchers considered a clear explanation of each part of articles about costing. Results: The results showed that the ABC system was unable to account for new issues, which is the reason researchers presented the new TDABC method. Some advantages of this system are its simple and updatable system, its usability in large and small companies for both simple and complex processes, economic evaluation of activities and performance assessment. Conclusion: The successful implementation of the TDABC model would provide an accurate cost report for goods and services, helping managers to evaluate the performance of diagnostic departments.